2021
DOI: 10.3390/sexes2010010
|View full text |Cite
|
Sign up to set email alerts
|

Central Precocious Puberty in Boys and Girls: Similarities and Differences

Abstract: Central precocious puberty (CPP) is due to the premature activation of the hypothalamic–pituitary–gonadal axis, which is responsible for the appearance of secondary sexual characteristics. It occurs before the age of 8 and 9 in girls and boys, respectively. CPP shows higher incidence in females than in males. Causes of CPP are similar in both sexes, but the idiopathic form is more frequent in girls, while organic forms are more frequent in males. Recent studies demonstrated a role of some genetic variants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…In order to confirm clinical findings, as well as to differentiate central from peripheral causes of precocious puberty, biochemical evaluation is usually obtained. Although a random basal LH level of >0.3 IU/L is generally considered diagnostic for CPP [29], Mucaria et al summarized reports of other suggested LH cut off levels for the diagnosis of CPP [30].…”
Section: Diagnosis and Treatment Of Central Precocious Pubertymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to confirm clinical findings, as well as to differentiate central from peripheral causes of precocious puberty, biochemical evaluation is usually obtained. Although a random basal LH level of >0.3 IU/L is generally considered diagnostic for CPP [29], Mucaria et al summarized reports of other suggested LH cut off levels for the diagnosis of CPP [30].…”
Section: Diagnosis and Treatment Of Central Precocious Pubertymentioning
confidence: 99%
“…In children with lower levels of LH but with physical manifestations concerning for progressive pubertal development, GnRH stimulation testing with leuprolide allows evaluation of LH and sex steroid response and may aid in distinguishing between central and peripheral precocious puberty [30,31]. Leuprolide stimulation is considered the gold standard in evaluating CPP; however, there are several cut-offs for leuprolide-stimulated LH levels that have been proposed, ranging from 5-8 IU/L, to indicate centrally mediated pubertal development [30,32].…”
Section: Diagnosis and Treatment Of Central Precocious Pubertymentioning
confidence: 99%